Design, validation and implementation of schematic diagrams and illustrations as a learning tool for blood and faecal samples collection in goats and cattle - Lui Xin Yen (2023)
Blood and faecal samples are the primary samples used in disease diagnosis and herd health evaluation of goat and cattle. There is a lack of instructional material regarding the sampling in FPV,UMK. This study aims to develop a learning module on blood and faecal sample collection in goat and cattle for easier reference in FPV,UMK. Design of illustrations and schematic diagrams were done by using digital drawing software and designing websites. For the validation of the design, face validation was done by collecting feedback from undergraduate students on a face–to-face basis after reviewing the design. Content validation was done by providing a self-administered online questionnaire for pre-clinical undergraduate veterinary students and two academicians in FPV,UMK to assess the influence of the design in improving understanding. Data were analysed by using Google Sheets and SPSS software and the result concluded that the veterinary students achieve better understanding on blood sampling (mean score 4.78 out of 5) and faecal sampling (mean score 4.77 out of 5) after review of the design. Lastly, implementation of the design was done by compiling them into a user-friendly learning module in electronic form and physical form. In conclusion, the use of the learning manual can improve understanding and solve the problem of heterogeneity and confusion from various references.